2000
DOI: 10.1021/ef990215y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Pyrolysis Reactivity and Aromatic Structure of Coal

Abstract: Illinois No. 6 coal was depolymerized by treatment with trifluoromethanesulfonic acid in methylcyclopentane at 120 °C. The yield of tetrahydrofuran (THF) extract was increased to 89 wt %. This increase was explained by the cleavage of bridges between aromatic units. The extract (TS d fraction) was further hydrogenated using a Ru/carbon catalyst in a mixed solvent of THF and acetic acid at 120 °C for 12-72 h under a hydrogen pressure of 10 MPa. Phenolic resin and polystyrene samples were used as references and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The results were in accord with those from the literature. Takagi and co-workers declared that there was a relationship between the H/C ratio and aromaticity of biochar or coal. , As mentioned above, the H/C and O/C molar ratio of pine declined with increasing torrefaction severity. Pine mainly underwent dehydration and aromatization reactions during torrefaction, thus causing the decreases in H/C molar ratio and the increases in aromaticity of pine.…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results were in accord with those from the literature. Takagi and co-workers declared that there was a relationship between the H/C ratio and aromaticity of biochar or coal. , As mentioned above, the H/C and O/C molar ratio of pine declined with increasing torrefaction severity. Pine mainly underwent dehydration and aromatization reactions during torrefaction, thus causing the decreases in H/C molar ratio and the increases in aromaticity of pine.…”
Section: Results and Discussionmentioning
confidence: 90%
“…However, there is a lack of quantitative information on the structural transformations of biomass during torrefaction and their influences on subsequent pyrolysis and gasification reactivity. Previous studies demonstrated that the pyrolysis and gasification reactivity of coal were related to its aromaticity or H/C molar ratio. , Hence, in the present study, the H/C molar ratio or aromaticity of biomass is attempted as an indicator of structural alteration of biomass during torrefaction, aiming to predict reactivity of torrefied biomass during pyrolysis/gasification. As shown in Figure , under different torrefaction conditions, biomass will proceed various reactions (such as dehydration, decarboxylation, and decarbonylation) with different severity to form cross-linking and charring biomass with varying H/C molar ratio and aromaticity, thus leading to the alterations in the pyrolysis/gasification reactivity of torrefied biomass.…”
Section: Introductionmentioning
confidence: 99%
“…15 In the past couple of decades, teams of researchers have proposed several structural parameters for evaluating the molecular structure of coal and other less-crystalline carbonaceous materials by the use of XRD. For example, the XRD proles of carbonaceous materials with low-crystallinity has been statistically interpreted by Hirsch 16 and Diamond; 17 Fujimoto and Shiraishi 18 modied the Diamond's method for estimating carbon-layer sizes; and Takagi 19 and Mennelia 20 used a standard analysis of the carbon stacking structure to understand the stacking structure of coal and other less-crystalline carbonaceous materials. Lu et al 21 conducted a systematic study on the evolution of L a of different types of coal, which proved that the development of L a was more dependent on coal rank.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is speculated that protonation of the hydroxyl group could occur in the weak acidic environment (in our case, pH around 3). 18 The protonated hydroxyl group could manipulate the electron density of the total compound causing a lowering of activation energy for the aromatic ring hydrogenation. Moreover, lowering the pH value of the system may promote the hydrogenolysis reaction since the elimination of the functional group could be catalyzed by acid.…”
Section: Hydrogenation Of Benzoic Acidmentioning
confidence: 99%